INSTANCE OF HERMAPHRODITISM IN THE ELECTRIC RAY, NARCINE TIMLEI (BLOCH AND SCHNEIDER) - Nair, R V; Soundararajan, R (Indian Journal of Fisheries, 2011)
A specimen of the electric ray, Narcine timlei, collected from the trawlcatches at Rameswaram on 12th November 1971, was found to be a hermaphrodite.The specimen measured 402 mm In total length. The Important fea^tures of the male and female reproductive "systems are described.